Cahiers de prison : cahiers 10, 11, 12, 13 - Gramsci, Antonio; Paris, Robert; Fulchignoni, Paolo; Granel, Gérard; Negri, Nino ([Paris] : Gallimard, 1978)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie